Testis structure, duration of spermatogenesis and daily sperm production in four wild cricetid rodent species (A. cursor, A. montensis, N. lasiurus, and O. nigripes). - Dirceu A Cordeiro (Public Library of Science (PLoS), 2021)
Although rodents represent approximately 40% of all living mammalian species, our knowledge regarding their reproductive biology is still scarce. Due to their high vulnerability to environmental changes, wild rodents have become beneficial models for ecological studies. Thus, we aimed to comparatively investigate key functional testis parameters in four sexually mature wild rodent species (A. cursor, A. montensis, N. lasiurus, and O. nigripes). These species belong to the Cricetidae family, which is the most diverse family of rodents in South America, with a total of ~120 species in Brazil. The results found for the gonadosomatic index and the sickled sperm head shape observed strongly suggest that the species here evaluated are promiscuous, prolific, and short-lived. The duration of spermatogenesis was relatively short and varied from ~35-40 days. Both the percentage of seminiferous tubules (ST) in the testis parenchyma (~95-97%) and the number of Sertoli cells (SC) (~48-70 million) per testis gram were very high, whereas a fairly good SC efficiency (~8-13 round spermatids per SC) was observed. In comparison to other mammalian species studied, particularly the rodents of the suborder Myomorpha (i.e. hamsters, rats and mice), the rodents herein investigated exhibited very high (~62-80 million) daily sperm production per testis gram. This impressive spermatogenic efficiency resulted mainly from the short duration of spermatogenesis and quite high values found for the ST percentage in the testis and the SC number per testis gram. We expect that the knowledge here obtained will help conservation programs and the proper management of wildlife.